2022
DOI: 10.1007/s00109-022-02234-y
|View full text |Cite
|
Sign up to set email alerts
|

Uremic mouse model to study vascular calcification and “inflamm-aging”

Abstract: Calcification and chronic inflammation of the vascular wall is a high-risk factor for cardiovascular mortality, especially in patients with chronic uremia. For the reduction or prevention of rapid disease progression, no specific treatment options are currently available. This study aimed to evaluate an adenine-based uremic mouse model for studying medial vessel calcification and senescence-associated secretory phenotype (SASP) changes of aortic tissue to unravel molecular pathogenesis and provide a model for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Vascular calcification acts as a complex inflammatory pathology in CKD. Accumulating reports indicated that patients with CKD are exposed to numerous uremic toxins and significantly elevated phosphate, which drives cellular calcification [ 30 , 31 ]. Hyperphosphatemia also unbalanced the oxidant/antioxidant process, which leads to vascular senescence and potentiates vascular inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification acts as a complex inflammatory pathology in CKD. Accumulating reports indicated that patients with CKD are exposed to numerous uremic toxins and significantly elevated phosphate, which drives cellular calcification [ 30 , 31 ]. Hyperphosphatemia also unbalanced the oxidant/antioxidant process, which leads to vascular senescence and potentiates vascular inflammation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was accompanied by a downregulation of the osteogenic marker, osterix ( 26 ). Furthermore, the pro-inflammatory secretome (SASP) derived from senescent cells has been found to elevate in both uremic mouse models and patients ( 58 , 59 ). However, the direct impact of SASP on vascular cells remains underexplored, with potential mechanisms possibly involving the propagation of senescence or amplification of localized inflammation.…”
Section: Role Of Cell Senescence In Vascular Calcification: Insights ...mentioning
confidence: 99%
“…Subsequently, this model was constructed using mice with a modified diet containing casein to maintain appetite [ 24 ]. Tölle et al fed female DBA2/N mice with an adenine diet containing 2% adenine, 6% protein, 1% calcium, and 1% phosphorus and observed gradual calcification of the vascular walls of the abdominal aorta, renal artery, and most prominently the thoracic aorta starting from week 9 [ 25 ]. Similarly, Zhang et al noted large-vessel calcification in the adenine mouse model, along with calcification of the heart valve and glomerular and tubular basement membranes.…”
Section: Reviewmentioning
confidence: 99%